Promise of Real-World Evidence for Patient Centricity in Gulf Cooperation Council Countries: Call to Action - Mohamed Nasr Mahmoud Hassan Farghaly; Ibrahim Sulaiman Mas'oud Al Ghaithi; Wael Abdel Rahman Mahamid; Abdallah Adlan; Saleh Mohammed AlGhamdi; Thamir M. Al Shammari; Nasser Mohammed Alqahtani; Suliman A. Al Ghnam; Marie Sleiman Awad Ibrahim; Hajer Al Mudaiheem; Mohamed Zahir Chouikrat; Yahia Aktham; et al. (Adis, Springer Healthcare, 2022)
Abstract Presently, Gulf Cooperation Council countries are lagging in the generation of real-world data and use of real-world evidence for patient-centered care compared with the global average. In a collaborative effort, experts from multiple domains of the healthcare environment from the Gulf Cooperation Council countries came together to present their views and recommended key action points for the generation of robust real-world data and leveraging real-world evidence in the countries. The opinions of the experts are presented, along with existing barriers to the effective generation of real-world evidence in the countries. The Gulf Cooperation Council countries are undergoing transformative changes paving the way for improved healthcare measures; however, the challenges in generating reliable, robust, accessible, and secure real-world evidence are persistent. Hence, ongoing public-private engagements, as well as collaborations between regulators, policymakers, healthcare professionals, insurance and pharmaceutical companies, and patients, are warranted. A few notable examples of real-world evidence studies highlighting the benefits of real-world evidence for gaining valuable insights into patient-centric decision making are also discussed. The actionable steps identified for successful real-world evidence generation would provide long-term, real-world evidence-based patient-centric benefits for the countries.